Impact and Mitigation Measures of COVID-19 towards Food Security Through Participation in Forest Management by Community in Sook, Keningau District, Sabah - Atin, Vilaretti; Lintangah, Walter (Forestry Faculty, Universitas Hasanuddin, 2023)
The COVID-19 pandemic has significantly impacted food security for the people due to the imposition of stringent measures to halt the spread of COVID-19 transmission. This study aimed to measure the community's perception of the level of COVID-19 impacts on their food security and to identify the community's participation in forest management around the Forest Management Unit (FMU) in Sook, Keningau District of Sabah, to improve their livelihood. A mixed-method approach was conducted where a total of 122 respondents were sampled using a questionnaire survey, focus group discussion with communities, and expert interviews to gather more valuable data. The result showed that the communities were primarily involved in forest management through employment, empowerment, capacity building, and decision-making, which could indirectly contribute to their food security. Meanwhile, the impacts of the COVID-19 transmission were found to moderately affect the people who live inside or adjacent to the forest. The impacts could be explained based on eight themes as the outcome of Principal Component Analysis (PCA): market access, food storage and safety, resource availability, adequate nutrition, food aid, affordability, continuous food supply, and food adaptation to shock. Communities were mainly involved in agricultural practices and could obtain resources from the forest to supplement their daily need. The communities raise a prominent issue regarding land tenure that needs to be resolved; thus, it is suggested that imperative action be considered to create a balance between conservation, economy, and social responsibilities.